Two Patient Studies of a Companion Diagnostic Immuno-Positron Emission Tomography (PET) Tracer for Measuring Human CA6 Expression in Cancer for Antibody Drug Conjugate (ADC) Therapy. (23rd October 2020) - Natarajan, Arutselvan; Srinivas, Shyam M.; Azevedo, Carmen; Greene, Lacey; Bauchet, Anne-Laure; Jouannot, Erwan; Lacoste-Bourgeacq, Anne-Sophie; Guizon, Isabelle; Cohen, Patrick; Naneix, Anne-Laure; Ilovich, Ohad; Cisneros, Jordan; et al.
An antigen binding fragment (BFab) derived from a tumor-associated mucin 1–sialoglycotope antigen (CA6) targeting antibody (huDS6) was engineered. We synthesized a companion diagnostic positron emission tomography (PET) tracer by radiolabeling BFab with [ 64 Cu] to measure CA6 expression on cancer tissues prior to anti-human CA6 (huDS6-DM4 antibody-drug conjugate) therapy for ovarian and breast cancer patients. After chemotherapy, the ovarian patient received PET scan with 18 F-2-fluoro-2-deoxyglucose ([ 18 F]FDG: 10 mCi), followed by [ 64 Cu]-DOTA-BFab ([ 64 Cu]BFab; 5.5 mCi) 1 week later for PET scanning of CA6 expression and subsequent surgery. The breast cancer patient was treated with chemotherapy before primary tumor resection and subsequent [ 18 F]FDG-PET scan. 4 weeks later the patient received of [ 64 Cu]BFab (11.7 mCi) for CA6 PET scan. Whole body [ 18 F]FDG-PET of the breast cancer patient indicated FDG-avid tumor metastases to the liver, bilateral hila and thoracic spine, but no uptake was observed for the ovarian patient. Each patient was also imaged by PET/CT with [ 64 Cu]BFab at 1 and 24 hours after tracer administration. The [ 64 Cu]BFab tracer was well tolerated by both patients without adverse effects, and no significant tracer uptake was observed in both patients. Immunohistochemistry (IHC) data indicated CA6 expressions were weak to intermediate and matched with the [ 64 Cu]BFab-PET signals.